HUBUNGAN ANTARA GRIT DENGAN RESILIENSI AKADEMIK PADA MAHASISWA YANG KULIAH SAMBIL BEKERJA - Grace Trixie Joceline Putri; Evanytha, Evanytha; Aini, Farida (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
Education is an important thing that can improve and develop individual potential, so it takes an effort to achieve everything. If students who study while working do not have good grit skills, it will have a negative impact on their academic resilience. This study aims to determine the relationship between grit and academic resilience in students who study while working. This research adopts a quantitative method involving 379 respondents in the JABODETABEK area. The measuring instrument used in this study were the grit scale and the academic resilience scale (ARS-30). The analysis method in this study uses the Spearman rank-order correlation test, because the data obtained in this study were not normally distributed. The research findings indicate a significant positive correlation between grit and academic resilience (p = 0.000) with a correlation coefficient of r = 0.496. Thus, it can be concluded that higher levels of grit correspond to increased academic resilience among students who study while working.